Piezoresistive effect in embedded thick-film resistors. Issue 1 (4th February 2019) - Borecki, Janusz; Araźna, Aneta; Janeczek, Kamil; Kalenik, Jerzy; Kalenik, Michał; Stęplewski, Wojciech; Tarakowski, Rafał
Abstract : Purpose: Nowadays, using of material properties for monitoring of phenomena occurring in the surrounding environment is very desirable. Taking into account the dynamic development of Internet of Things and the technological development of printed electronics, research into the using of printed electronic components for sensor applications can be one of the most prominent directions of searching for new innovative solutions. Among others, it is possible to apply them to produce the strain gauges, as well as for construction of advanced sensors for medical applications. The goal of this paper is to present the possibilities and using different constructions of embedded polymer thick-film resistors as the sensors of tension or strain. Design/methodology/approach: The investigations were based on the polymer thick-film resistors made of carbon or carbon–silver inks printed on copper pads made on FR-4 material on two sides. The longitudinal samples laminated with resin-coated copper foil material and without lamination were bent on a strength machine. During the tests, the resistors depending on their placement were stretched or compressed. Some of the samples were also tested under high pressure. Under the influence of applied stresses, there was a reversible change in electrical resistance, which was monitored. Findings: The study showed that the polymer thick-film resistors are characterized by a measurable piezoresistive effect. By analyzing the value of the observed resistance changes, a magnitude of strain or pressure can be worked out. During the bending, the piezoresistive effect depends on the location and orientation of the resistor. After stopping of the mechanical strains, the electrical resistance of the resistive elements does not return exactly to the initial value. This is probably related to the substrate material and the resistive paste composition. The results are very promising and further research will be done. Originality/value: The results provided information about the piezoresistive effect of polymer thick-film resistors printed on the deformable substrate which could be interesting for engineers involved in printed sensor development dedicated for different fields of application. This phenomenon can be used to manufacturing cheap and uncomplicated sensors to monitor deformation. There are several aspects to be solved, but with the use of new types of resistive pastes and substrates, there is a potential possibility of using such resistors as sensors.